2013
DOI: 10.1149/05701.1289ecst
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Electrodes for Intermediate Temperature Proton Conducting Fuel Cell

Abstract: In order to develop efficient Protonic Ceramic Fuel Cell, different composite electrodes made of BaCe0.9Y0.1O3 and NiO or mixed ionic-electronic conductor (BSCF) were investigated as anode and cathode respectively. Ni-BCY composite synthesized by combustion offers sufficient open porosity, shows an electrical conductivity superior to 1000 S.cm-1 and a very low ASR value (0.06 Ω.cm2 at 600°C). The electrochemical properties of BSCF-BCY composite cathode have been studied and the obtained ASR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…One of the first examples, in 2009, is a BSCF-BCZY71 composite prepared by a modified Pechini method, which provided an MPD of 0.42 W•cm −2 and a low R p of 0.1 Ω•cm 2 at 700 • C with a BCZY71 electrolyte [148]. Taillades et al [149] then showed that a composite BSCF-BCY10 exhibited a lower ASR value (0.53 Ω•cm 2 at 600 • C) compared to pure BSCF. The same group subsequently fabricated a BSCF-BZCYYb1711 cathode deposited on a BCZYYb7111 electrolyte by wet powder spraying, achieving an MPD of 0.422 W•cm −2 at 600 • C [150].…”
Section: Composite Cathodesmentioning
confidence: 99%
“…One of the first examples, in 2009, is a BSCF-BCZY71 composite prepared by a modified Pechini method, which provided an MPD of 0.42 W•cm −2 and a low R p of 0.1 Ω•cm 2 at 700 • C with a BCZY71 electrolyte [148]. Taillades et al [149] then showed that a composite BSCF-BCY10 exhibited a lower ASR value (0.53 Ω•cm 2 at 600 • C) compared to pure BSCF. The same group subsequently fabricated a BSCF-BZCYYb1711 cathode deposited on a BCZYYb7111 electrolyte by wet powder spraying, achieving an MPD of 0.422 W•cm −2 at 600 • C [150].…”
Section: Composite Cathodesmentioning
confidence: 99%
“…The analysis of what happens at the interface between proton-conducting electrolytes and electrodes is necessarily related to the different device fabrication procedures and to the specific electrolyte-electrode couples. The assembly of a proton-conducting oxide with air electrodes already designed for O-SOC devices was initially pursued and continues to this day. A straightforward method to assess the electrode–electrolyte reactivity is by mixing the two compounds, forming a pellet to ensure the closest contact, annealing at a suitable temperature for a given time, and then carrying out an XRD measurement. This procedure is frequently exploited: in some cases, a shift of diffraction peaks is observed, originated by diffusion into the host matrix of cations with a different size compared to the regular species; in other cases, the growth of a new phase may occur, , or the stability of the involved oxides is eventually demonstrated .…”
Section: Cathode Interfacesmentioning
confidence: 99%
“…Cermets consisting of Ni and a proton-conducting oxide, such as Ni-BCY [20] and Ni-BCZY [21], are frequently used as the anode materials in PCFCs. Studies on PCFC anodes have demonstrated that the proton conductivity of the proton-conducting oxide phase strongly affects the anodic properties.…”
Section: Introductionmentioning
confidence: 99%